ANALYSIS OF THE QUALITY OF PHARMACEUTICAL SERVICES ON THE SATISFACTION OF PATIENTS WITH TYPE 2 DIABETES MELLITUS AT ROYAL PRIMA HOSPITAL, MEDAN CITY - Simanjuntak, Mafe Robbi; Yuliandini, Marsheila; Hulu, Victor Trismanjaya (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
Type 2 Diabetes Mellitus (DMT2) is one of the non-communicable diseases with high prevalence in Indonesia and requires long-term treatment management. Pharmaceutical services have an important role in supporting DMT2 treatment, but the results of the initial survey show that some outpatients at Royal Prima Hospital Medan are not satisfied with the services provided. This study aims to analyze the relationship between the quality of pharmaceutical services and the level of satisfaction of DMT2 patients. This study used a quantitative design with a cross-sectional approach, involving 100 DMT2 outpatient respondents. Data was collected using questionnaires that have been tested for validity and reliability. The results of the univariate analysis showed that most respondents rated the aspects of physical facilities (83%), reliability (82%), assurance (85%), and empathy (85%), but responsiveness was rated as poor (53%). As many as 90% of respondents were satisfied with the service as a whole. The results of bivariate analysis showed that there was a significant relationship between all dimensions of pharmaceutical service quality and patient satisfaction (p<0.05). Multivariate analysis identified that physical means (OR=2.240; p=0.027) and assurance (OR=2.767; p=0.007) were the most influential factors on patient satisfaction. This study concludes that the quality of pharmaceutical services has a significant effect on DMT2 patient satisfaction, with recommendations for increasing responsiveness as a top priority.